Assessing variability in breast cancer management across the world: results of a questionnaire survey amongst global international experts in breast cancer management - GÜLLÜOĞLU, MAHMUT BAHADIR (My University, 2022)
Background: Breast cancer is the most common cancer in women worldwide with an estimated 2.3 million breast cancer cases diagnosed annually. The outcome of breast cancer management varies widely across the globe which could be due to a multitude of factors. Hence, a blanket approach in standardisation of care across the world is neither practical nor feasible.Aim: To assess the extent and type of variability in breast cancer management across the globe and to do a gap analysis of patient care pathway.Method: An online questionnaire survey and virtual consensus meeting was carried out amongst 31 experts from 25 countries in the field of breast cancer surgical management. The questionnaire was designed to understand the variability in diagnosis and treatment of breast cancer, and potential factors contributing to this heterogeneity.Result: The questionnaire survey shows a wide variation in breast surgical training, diagnosis and treatment pathways for breast cancer patients. There are several factors such as socioeconomic status, patient culture and preferences, lack of national screening programmes and training, and paucity of resources, which are barriers to the consistent delivery of high-quality care in different parts of the world.Conclusion: On-line survey platforms distributed to global experts in breast cancer care can assess gaps in the diagnosis and treatment of breast cancer patients. This survey confirms the need for an in-depth gap analysis of patient care pathways and treatments to enable the development of personalised plans and policies to standardise high quality care.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Health Sciences; ONKOLOJİ; Klinik Tıp; Klinik Tıp (MED); ONCOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); breast cancer; global health; questionnaire; socioeconomic status; training; STATISTICS